THE RELATIONSHIP BETWEEN LEARNING STYLE AND EMOTIONAL INTELLIGENCE WITH THE ABILITY TO MEMORIZE THE QUR'AN IN CLASS X MAN 2 MEDAN MODEL STUDENTS - Ulfa Khairani (ANSIRU PAI : Pengembangan Profesi Guru Pendidikan Agama Islam, 2019)
This study aims to determine and describe: (1) the relationship of learningstyles with the ability of students to memorize the Qur'an in class X IPSMAN 2 Medan model, (2) the relationship of emotional intelligence withthe ability of students to memorize the Qur'an in class X IPS MAN 2Medan Model, and (3) the relationship between learning styles andemotional intelligence with the ability of students to memorize the Qur'anin class X IPS MAN 2 Medan Model. The study was conducted atMadrasah Aliyah Negeri 2 Model Medan. This research is a quantitativestudy using the correlation research method. The population in this studywere all social studies students of class X consisting of 5 classes with atotal of 186. A sample of 20% of students totaling 186 namely 37.2 rounded37 students taken at random (random sample). Data collectioninstruments used were questionnaires and tests. Analysis of the data usedis correlation and regression. The research findings show: (1) there is apositive and significant relationship between learning styles with theability to memorize the Qur'an with a correlation number of 0.393 with theequation of the regression line Ŷ = 77,15 + 0.12X1, (2) there is a positiveand significant relationship between emotional intelligence with theability to memorize the Qur'an with a correlation number of 0.519 with theequation of the regression line Ŷ = 66,26 + 0.27X2. and (3) there is apositive and significant relationship between learning styles andemotional intelligence with the ability to memorize the Qur'an with acorrelation number of 0.589 with the equation of the regression line Ŷ =35,56 + 0.09 X1 + 0.24X2. Effective contribution of learning style variables tothe ability to memorize the Qur'an is 12,20%, while the effectivecontribution of the variable of emotional intelligence with the ability tomemorize the Qur'an is 23,90%.